Pengaruh Transfer pricing, Kepemilikan Asing, dan Intensitas Modal Terhadap Penghindaran Pajak - Imron, Malinda Aliffiyah Akbar; Durya, Ngurah Pandji Mertha Agung; Mardjono, Enny Susilowati; Suhartono, Entot (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study analyzes the influence of transfer pricing, foreign ownership, and capital intensity on tax avoidance in the multinational energy companies listed on the Indonesia Stock Exchange (IDX) during 2019-2023. The independent variables analyzed include transfer pricing, measured by related party receivables to total receivables; foreign ownership, measured by foreign-owned shares to total shares; and capital intensity, measured by net fixed assets to total assets. The dependent variable, tax avoidance, is calculated using the Effective tax rate (ETR). The research sample consists of 21 multinational energy companies listed on the IDX during the specified period, and the data were analyzed using multiple linear regression analysis. The findings indicate that transfer pricing and capital intensity significantly affect tax avoidance. However, foreign ownership does not have a significant influence on tax avoidance.